The motivational foundations of childbearing: Investigating relationships between childbearing attitudes, value preferences, and parental bonding - Eugene Tartakovsky; Mor Mizrahi (PLoS ONE, 2025)
This study aims to reveal the motivational foundations of childbearing. To achieve this goal, we investigated how general motivational goals expressed in personal value preferences and relationships with one’s parents are connected to attitudes toward childbearing. The study is based on Schwartz’s theory of values [1]. The study was conducted in Israel among young adults (age 18–35) with no children (n = 1122). Higher preferences for tradition and benevolence-care and lower preferences for self-direction and universalism-nature values were associated with positive childbearing attitudes among men and women. In addition, higher preferences for security-social values were associated with positive childbearing attitudes among men. Maternal bonding was associated with positive childbearing attitudes among men and women, and paternal bonding was associated with positive childbearing attitudes among men. High religiosity, high income, and low education were associated with positive childbearing attitudes among women. Among men, only the effect of religiosity was significant. No difference between men and women in childbearing attitudes was found. Personal value preferences partly mediated the effects of parental bonding and socio-demographic variables on childbearing attitudes. The obtained results advance our understanding of the psychological mechanisms of childbearing.